(3fRgI GdCUMGH (B( (3aj GdgjFI (B)s - (3eMeO Hf SdjeGf Hf SYO Hf eSYhO GdcGajLj GdQhej GdMfaj, eMjj GdOjf, CHh YHO Gddg, J (B879 (3g` s
(3ChdgG (B:s
(3GdMeO ddg YXje GdTCf hHYO aCbhd (B: (3bGd Gddg JYGdi hbGd GdfHi (B((3U(B) (3aEf bdJ aeG GdCQV ? bdJ gi LSe HGQO hjGHS EPG GNdi hWHYg s
(3BNQgG (B:s
(3Cf Cgd GdgfO RYehG Gf OhQGdGQV SHYI GdGa heFI aQSM Ydi QCi GdHYV GJjJc HGdJhMjO GQLh JaVdG aYahc jG QH GdHQjI hGSY hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3HBNQgG Jedc eDQN ai (B1034(3g`s
(3HgG HYV GdQShe hGdNQGFWs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B51 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B209s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B138 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
Keywords: (3Gdadcs